PENERAPAN METODE INDEX CARD MATCH UNTUK MENGIMPLEMENTASIKAN 4C (CRITICAL THINKING, COMMUNICATION, COLLABORATION, AND CREATIVITY) PADA PEMBELAJARAN PJOK - Muhammad Hafizalfiqri; Aref Vai; Muhammad Imam Rahmatullah (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study examines how well sixth-grade students at SDIT Az-Zuhra, Pekanbaru, use the Index Card Match method to improve their 4C skills Critical Thinking, Communication, Collaboration, and Creativity in Physical Education, Sports, and Health (PJOK). The research was carried out across four sessions, split into two cycles, each consisting of two meetings, using a Class Action Research (CAR) methodology. Data was gathered from observations, interviews, and recording of the 28 students who took part. Students first demonstrated poor competency in all four C skills during the pre-cycle period, mostly as a result of the preponderance of passive learning techniques. Despite modest advancements in teamwork, critical thinking, communication, and creativity were still below par in the first cycle, which was ascribed to difficulties in applying the Index Card Match approach. By the second cycle, however, notable improvements were seen, with students exhibiting excellent communication and teamwork abilities as well as strong growth in critical thinking and creativity. According to the results, the Index Card Match approach greatly aids in the development of critical 21st-century abilities and promotes active learning. In order to further encourage skill enhancement in educational settings, this study suggests that interactive teaching approaches be used and improved.